Securing electronics healthcare records in Healthcare 4.0 : A biometric-based approach. (June 2019) - Hathaliya, Jigna J; Tanwar, Sudeep; Tyagi, Sudhanshu; Kumar, Neeraj
Abstract: In recent years, there has been an exponential increase in the usage of Healthcare 4.0-based diagnostics systems across the globe. In healthcare 4.0, the patient's records are stored in electronic health record (EHR) repository which may be loacted either at a centralized or distributed locations to help the Doctors to easily access the patient's healthcare data from anywhere at any time. As this data is accessed from the database repository using an open channel, i.e., the Internet, so, security and privacy are major concerns while accessing it from any location. Motivated from these facts, in this paper, we propose a biometric-based authentication scheme to ensure secure access of the patients EHR from any location. In the proposal, we first identified various security threats and challenges in accessing EHR from the database repository. Then, the secure biometric-based scheme is designed which is validated using the Automated Validation of Internet Security Protocols and Applications (AVISPA) tool. The results obtained demonstrated that the proposed scheme is superior (in terms of computation and communication costs) in comparison to the traditional state-of-the-art existing schemes.